Lacosamide as monotherapy in focal seizure: Literature review - Sonkusare, Kishore R.; Barkate, Hanmant V. (International Journal of Epilepsy, 2017)
Lacosamide is a newer approved antiepileptic drug (AED) characterized by its novel pharmacodynamic profile. It is now approved by United States Food and Drug Administration for use as monotherapy in adults (aged>17 years) with focal seizures based on historical controlled trial by Wechsler RT et al in 2014. Randomized controlled trials on lacosamide monotherapy have demonstrated significant reduction in median seizure frequency. In addition, 50% responder rates for lacosamide was noted in half of the patients, with retention rate in two third of patients in 1 year follow up period. Adverse events reported in clinical trials were mostly mild to moderate in intensity. The most common adverse events were dizziness, headache, convulsion, nausea and fatigue while convulsion and dizziness were commonly responsible for drug discontinuation. Overall, lacosamide monotherapy can be a good treatment option in patients with focal seizure.
Keywords: Lacosamide; Monotherapy; Historical controlled trial; Focal seizure